2000
DOI: 10.1002/(sici)1097-0215(20000501)86:3<337::aid-ijc6>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the transcription factors CCAAT-enhancer binding protein-? (C/EB?) and C/EBP? (CHOP) correlate with invasiveness of human colorectal cancer

Abstract: Regulation of cell differentiation is most often impaired in malignant tumors and may represent a key mechanism for the progression of the disease. CCAAT‐enhancer binding protein (C/EBP) is a family of transcription factors involved in the regulation of embryonic gut development in rodents, which has also been detected in various malignancies, e.g., liposarcomas and breast and ovarian epithelial tumors. We studied the relationship between C/EBP and tumor histology (Duke's invasive stage and pathological grade)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 33 publications
(41 reference statements)
4
79
2
Order By: Relevance
“…Mutations in the apc or b-catenin genes lead to cytosolic accumulation of b-Catenin, increased transcriptional activity of the b-Catenin/TCF complex and eventually to uncontroled proliferation (for review see Peifer and Polakis, 2000;Clevers, 2004). CHOP is upregulated in some colorectal cancers, and correlates with the invasiveness of these tumours in situ (Rask et al, 2000). However, the available evidence strongly indicates that CHOP is an antiproliferative and proapoptitic protein (Barone et al, 1992;Maytin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the apc or b-catenin genes lead to cytosolic accumulation of b-Catenin, increased transcriptional activity of the b-Catenin/TCF complex and eventually to uncontroled proliferation (for review see Peifer and Polakis, 2000;Clevers, 2004). CHOP is upregulated in some colorectal cancers, and correlates with the invasiveness of these tumours in situ (Rask et al, 2000). However, the available evidence strongly indicates that CHOP is an antiproliferative and proapoptitic protein (Barone et al, 1992;Maytin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of CHOP and C/EBPb correlate with the invasiveness of human colorectal cancer (Rask et al, 2000), and the cancer chemopreventive substance curcumin enhances CHOP expression in colonocytes (HCT-116) containing a mutant b-Catenin (Scott and Loo, 2004). Curcurmin treatment of HCT-116 cells impairs b-Catenin/TCF-LEF signalling at different steps in these cells, resulting in growth arrest and apoptosis (Jaiswal et al, 2002), but the cellular mediators of this effect remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, overexpression of C/EBPb-2 in a human mammary epithelial cell line lead to anchorage independence and invasive properties (Bundy and Sealy, 2003). C/EBPb is highly expressed in colorectal tumors (Rask et al, 2000) and is associated with ovarian tumor progression (Sundfeldt et al, 1999). Furthermore, C/EBPb can interact with cyclin D1 and appears to be important for the unique pattern of altered gene expression in human cancers that overexpress cyclin D1 (Lamb et al, 2003).…”
mentioning
confidence: 99%
“…As a result of the high degree of conservation in their bZIP domains, C/EBP family members form both homodimers and heterodimers (Rask et al, 2000). C/EBPd, another member of the C/EBP family, is upregulated in mouse skin papillomas and squamous cell carcinomas (Kim and Fischer, 1998).…”
mentioning
confidence: 99%
“…In Wilms' tumors, or nephroblastomas, C/EBPb is expressed at high levels in relapsing and metastatic tumors and blocking C/EBPb expression in a Wilms' tumor cell line results in spontaneous apoptosis (Li et al, 2005). Increased expression of C/EBPb is associated with human breast, colorectal and ovarian tumorigenesis (Sundfeldt et al, 1999;Rask et al, 2000;Bundy and Sealy, 2003). In addition, cyclin D1 can interact with C/EBPb to alter gene expression and there is evidence that this interaction is required for the unique patterns of gene expression observed in human cancers that overexpress cyclin D1 (Lamb et al, 2003).…”
Section: Introductionmentioning
confidence: 99%